2017
DOI: 10.1186/s12944-017-0627-y
|View full text |Cite
|
Sign up to set email alerts
|

The small dense LDL particle/large buoyant LDL particle ratio is associated with glucose metabolic status in pregnancy

Abstract: BackgroundThe lipoprotein subfraction particle profile can be used to improve clinical assessments of cardiovascular disease risk and contribute to early detection of atherogenic dyslipidemia. Lipid alterations in gestational diabetes have been extensively studied, but the results have been inconsistent. Here, we investigated serum lipoprotein subfraction particle levels and their association with glucose metabolic status in pregnancy.MethodsTwenty-eight pregnant women with gestational diabetes and 56 pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Moreover, our study found that patients with GDM had much higher levels of TG and lower levels of LDL, consistent with previous studies (36)(37)(38)(39)(40). The precise mechanism of lower LDL in women with GDM was unclear.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, our study found that patients with GDM had much higher levels of TG and lower levels of LDL, consistent with previous studies (36)(37)(38)(39)(40). The precise mechanism of lower LDL in women with GDM was unclear.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Srisawasdi and colleagues' study proposed the ratio of sdLDL-C to lbLDL-C as an excellent biomarker for evaluating lipid metabolic status in patients with metabolic syndrome (25). Chen et al reported that sdLDL-C/lbLDL-C ratio was associated with glucose metabolic status in pregnancy (26). Interestingly, we also found LDLC-1 was negatively correlated with LDLC-3 to LDLC-7.…”
Section: Discussionsupporting
confidence: 53%
“…Studies have shown that even mild hyperglycemia during pregnancy is associated with an increase in perinatal complications [ 22 , 23 ]. Although the adverse effects of GDM on the mother and fetus are widely known, there are still many unresolved issues regarding GDM [ 24 ]. Therefore, the WHO states that there are many ambiguities about the various strategies for screening for GDM.…”
Section: Discussionmentioning
confidence: 99%